Design and Analysis of a Novel Flexure-Based XY Micropositioning Stage - Chenlei Jiao; Zhe Wang; Bingrui Lv; Guilian Wang; Weiliang Yue (Applied Sciences, 2020)
Flexure-based micropositioning stages with high positioning precision are really attractive. This paper reports the design and analysis processes of a two-degree-of-freedom (2-DOF) flexure-based XY micropositioning stage driven by piezoelectric actuators to improve the positioning accuracy and motion performance. First, the structure of the stage was proposed, which was based on rectangular flexure hinges and piezoelectric actuators (PZT) that were arranged symmetrically to realize XY motion. Then, analytical models describing the output stiffness in the XY directions of the stage were established using the compliance matrix method. The finite element analysis method (FEA) was used to validate the analytical models and analyze the static characteristics and the natural frequency of the stage simultaneously. Furthermore, a prototype of the micropositioning stage was fabricated for the performance tests. The output response performance of the stage without an end load was tested using different input signals. The results indicated that the stage had a single direction amplification capability, low hysteresis, and a wide positioning space. The conclusion was that the proposed stage possessed an ideal positioning property and could be well applied to the positioning system.